Cytologic Diagnosis of Infection in Pap Smear - Singkam, Sasithorn; Anacha, Suchittra (Siriraj Medical Bulletin, 2024)
Various organisms such as bacterial infections, fungal infections, protozoan, and viral infections can be detected in vaginal and cervical specimens collected for cervical cancer screening or Pap smear. Some organisms are sexually transmitted and cause infectious diseases in female genital tract and need to be treated but some are not. Organisms and cellular changes in Pap smear need carefully interpreted according to the Bethesda system for reporting cervical cytology 2014 because they mimic to other cellular changes from other causes and have some difficulty for interpretation. The current Bethesda reporting system divided infection into 4 major types as mention above. From 4 major types, we can classify and report the infection into 6 subtypes including trichomonas vaginalis (TV), fungal organisms morphologically consistent with Candida spp., shift in flora suggestive of bacterial vaginosis (BV), bacteria morphologically consistent with Actinomyces spp., cellular change consistent with herpes simplex virus (HSV), and the last one is cellular changes consistent with cytomegalovirus(CMV). The detection of organisms and cellular changes may help the clinicians to provide early treatment for infected woman before they have severe symptoms and can reduce transmission to their partners.